Occupational Risk of Work-Related Musculoskeletal Disorders in Healthcare and Non-Healthcare Workers - Aulia, Zahra Katrina; Welong, Katherina; Arda, Anggi Mutia; Aulia, Wima; Ulfah, Eriane (Frontiers on Healthcare Research, 2025)
Background: Work-related musculoskeletal disorders (WMSDs) are among the most common occupational health issues worldwide, significantly affecting worker productivity and well-being. This study aims to assess the prevalence and risk levels of WMSDs among various professions at Dr. M. Djamil General Hospital, Padang, highlighting high-risk occupations and proposing preventive strategies. Method: A cross-sectional study was conducted on 476 hospital staff using a proportional random sampling technique. The Nordic Body Map (NBM) Questionnaire was employed to identify musculoskeletal complaints, and data were analyzed using descriptive statistics. Ethical approval was obtained from the institutional review board (IRB), and informed consent was secured from all participants.. Result: Among the respondents, 7 individuals (1.5%) were identified as having a high risk of developing WMSDs, with the most affected professions being nutrition processors (n=3), hospital orderlies (n=2), and nurses (n=2). Severe pain was reported primarily in the lower back (9 respondents, 1.9%) and right leg (9 respondents, 1.9%), followed by the left leg (8 respondents, 1.7%). Conclusion: WMSDs pose a significant occupational health challenge, particularly among high-risk hospital staff. To mitigate these risks, ergonomic interventions, such as improved workstation design and periodic stretching exercises, should be implemented. Future research should explore additional risk factors, including workload and psychological stress, to develop more comprehensive preventive strategies.